Microarray analysis of serum mRNA in patients with head and neck squamous cell carcinoma at whole-genome scale - Čapková, Markéta; Šáchová, Jana; Strnad, Hynek; Kolář, Michal; Hroudová, Miluše; Chovanec, Martin; Čada, Zdeněk; Šteffl, Martin; Valach, Jaroslav; Kastner, Jan; Vlček, Čestmír; Smetana, Karel; et al. (BioMed research international, 2014)
With the increasing demand for noninvasive approaches in monitoring head and neck cancer, circulating nucleic acids have been shown to be a promising tool. We focused on the global transcriptome of serum samples of head and neck squamous cell carcinoma (HNSCC) patients in comparison with healthy individuals. We compared gene expression patterns of 36 samples. Twenty-four participants including 16 HNSCC patients (from 12 patients we obtained blood samples 1 year posttreatment) and 8 control subjects were recruited. The Illumina HumanWG-6 v3 Expression BeadChip was used to profile and identify the differences in serum mRNA transcriptomes. We found 159 genes to be significantly changed (Storey's P value <0.05) between normal and cancer serum specimens regardless of factors including p53 and B-cell lymphoma family members (Bcl-2, Bcl-XL). In contrast, there was no difference in gene expression between samples obtained before and after surgery in cancer patients. We suggest that microarray analysis of serum cRNA in patients with HNSCC should be suitable for refinement of early stage diagnosis of disease that can be important for development of new personalized strategies in diagnosis and treatment of tumours but is not suitable for monitoring further development of disease.
Keywords: demografie; Gene Expression Regulation, Neoplastic; Squamous Cell Carcinoma of Head and Neck; RNA, Messenger; Male; mikročipová analýza; dlaždicobuněčné karcinomy hlavy a krku; genom lidský; Demography; regulace genové exprese u nádorů; signální transdukce; Adult; nádory hlavy a krku; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; nádorový supresorový protein p53; messenger RNA; Head and Neck Neoplasms; analýza hlavních komponent; stanovení celkové genové exprese; Genome, Human; Signal Transduction; Gene Expression Profiling; Principal Component Analysis; lidé; ženské pohlaví; studie případů a kontrol; Humans; Tumor Suppressor Protein p53; Microarray Analysis; apoptóza; spinocelulární karcinom; Female; lidé středního věku; Apoptosis; Carcinoma, Squamous Cell; Middle Aged